Dynamics of Main Indicators of the Epidemiological Situation on Tuberculosis in the Omsk Region - L. V. Puzyryova; A. V. Mordyk; O. G. Ivanova; S. N. Rudneva; M. P. Tatarintseva (Эпидемиология и вакцинопрофилактика, 2017)
The aim of the study is to analyze the dynamics of the main epidemiological indicators that characterize the epidemiological situation of tuberculosis in the Omsk Region from 2001 to 2015. Material and methods. For the analysis were used for reporting forms: № 8 («Information on active tuberculosis», № 33 («Information on tuberculosis patients»), № 61 («Information on contingents of patients with HIV infection»). The statistical processing was carried out with the help of the Microsoft Excel software package, applied the method of analyzing the dynamic series with the calculation of the rates of growth/decrease in epidemiological indicators and the determination of the average geometric index for aligned series, regression analysis. Results. It has been established that in 2009 in the Omsk Region, the main indicators that characterize the epidemiological situation of tuberculosis have decreased: morbidity (by 25.4%), prevalence (by 55.5%), mortality (by 53.1%). At the same time, there was an increase in the incidence of multidrug-resistant disease, an increase in the incidence of HIV infection and HIV-associated tuberculosis. Conclusions. The obtained results allow to assume the possibility of developing a new period of worsening of the epidemiological situation of tuberculosis, characterized by high mortality and a further growth of the reservoir of infection in the region.